Intact neural activity during a Go/No‐go task is associated with high global functioning in schizophrenia. Issue 7 (2nd May 2016) - Araki, Tsuyoshi; Kirihara, Kenji; Koshiyama, Daisuke; Nagai, Tatsuya; Tada, Mariko; Fukuda, Masato; Kasai, Kiyoto
Abstract : Aim: Go/No‐go derived event‐related potential (ERP) signals have been widely used in schizophrenia research to monitor self‐control deficits in this disorder. However, no study to date has associated Go/No‐go‐related ERP with global functioning. Methods: Participants consisted of 21 patients with schizophrenia and 22 healthy controls. We used a visual Go/No‐go paradigm to measure Go/No‐go‐related N2/P3 ERP components by means of a 64‐electrode cap for electroencephalogram recording. We used the Global Assessment of Functioning to evaluate global functioning and analyzed the correlation between ERP indices and global functioning scores. Results: N2 amplitudes were reduced in patients with schizophrenia, but not influenced by either of the Go/No‐go conditions. P3 amplitudes were influenced by the Go/No‐go conditions, but not reduced in patients with schizophrenia. Global functioning was correlated with the No‐go P3 amplitudes, but not N2 amplitudes, in patients with schizophrenia. Conclusion: These results indicate that global functioning is associated with intact neural activity rather than impaired neural activity during Go/No‐go response inhibition tasks in patients with schizophrenia.